Glycal Assembly by the in situ Generation of Glycosyl Dithiocarbamates - Padungros, Panuwat (2012)
[Image: see text] Glycal assembly offers an expedient entry into β-linked oligosaccharides, but epoxyglycal donors can be capricious in their reactivities. Treatment with Et(2)NH and CS(2) enables their in situ conversion into glycosyl dithiocarbamates, which can be activated by copper triflate for coupling with complex or sterically congested acceptors. The coupling efficiency can be further enhanced by in situ benzoylation, as illustrated in an 11-step synthesis of a branched hexasaccharide from glucals in 28% isolated yield and just 4 chromatographic purifications.